Data quality of Glasgow Coma Scale and Systolic Blood Pressure in scientific studies involving physician‐staffed emergency medical services: Systematic review. Issue 7 (27th April 2020) - Tønsager, Kristin; Krüger, Andreas J.; Ringdal, Kjetil G.; Rehn, Marius
Abstract : Background: Emergency physicians on‐scene provide highly specialized care to severely sick or injured patients. High‐quality research relies on the quality of data, but no commonly accepted definition of EMS data quality exits. Glasgow Coma Score (GCS) and Systolic Blood Pressure (SBP) are core physiological variables, but little is known about the quality of these data when reported in p‐EMS research. This systematic review aims to describe the quality of pre‐hospital reporting of GCS and SBP data in studies where emergency physicians are present on‐scene. Methods: A systematic literature search was performed using CINAHL, Cochrane, Embase, Medline, Norart, Scopus, SweMed + and Web of Science, in accordance with the PRISMA guidelines. Reported data on accuracy of reporting, completeness and capture were extracted to describe the quality of documentation of GCS and SBP. External and internal validity assessment was performed by extracting a set of predefined variables. Results: We included 137 articles describing data collection for GCS, SBP or both. Most studies (81%) were conducted in Europe and 59% of studies reported trauma cases. Reporting of GCS and SBP data were not uniform and may be improved to enable comparisons. Of the predefined external and internal validity data items, 26%‐45% of data were possible to extract from the included papers. Conclusions: Reporting of GCS and SBP is variable in scientific papers. We recommend standardized reporting to enable comparisons of p‐EMS.